Tropical marine environment : charting strategies for the millennium :[proceedings] - International Conference on the Straits of Malacca (2nd : 2001 : Penang, Malaysia); Fatimah Md. Yusoff (Serdang : MASDEC Universiti Putra Malaysia, 2002)
10